Rhabdomyolysis after co-prescription of statin and fusidic acid. (9th October 2012) - Kearney, S; Carr, A S; McConville, J; McCarron, M O
Abstract : Avoid co-prescription of fusidic acid with statins to reduce the risk of rhabdomyolysis